Residential location, travel, and energy use in the Hangzhou Metropolitan Area - Petter Naess (Journal of Transport and Land Use)
This paper presents the results of a study examining the influence of residential location on travel behavior in the Hangzhou Metropolitan Area, China. The location of the dwelling relative to the center hierarchy of the metropolitan area is found to exert a considerable influence on the travel behavior of the respondents. On average, living close to the center of Hangzhou contributes to less overall travel, a higher proportion of trips by bicycle and on foot, and lower consumption of energy for transport. The location of the dwelling relative to the closest second-order and third-order center also influences travel, but not to the same extent as proximity to the city center. These geographical differences in travel behavior are independent of residential preferences and of attitudes toward transport and environmental issues, and therefore cannot be explained by residential self-selection.